(untitled) (Revista Espinhaço, 2020)
The paper analyzes some consequences of the My House, My Life Program for dwellers of two Social Housing Residentials in the city of Montes Claros/MG, emphasizing the strategies and/or adaptations used in everyday life by families to deal with limitations derived from the new housing context. Data from documents and field research unveiled social vulnerability situations, spatial segregation and lack of infrastructure. Access to homeownership brought about new perspectives for the appropriation of space and adaptation to reality. The paper concludes stressing the need for reviewing policy drivers towards granting the human social right to housing and dignity to these families.